LAY MINISTRY AND ORDAINED MINISTRY: COLLABORATION TO CORESPONSIBILITY - Bolanle, Ojo Anthonia (Asian Horizons, 2015)
The term ‘collaboration’ has been used to describe lay ministry in the Church since the Second Vatican Council. The laity were viewed as assisting the clergy in performing ‘their duties,’ mostly in the areas where there were shortage of priests. Nevertheless, this takes a new dimension when Pope Benedict XVI, on 26th May, 2009, addressing the Diocese of Rome used the term ‘co-responsibility’ as the most appropriate word to describe lay ministry in the Church. This shows that the ministry of the laity in the propagation of the Kingdom of God is more than mere participation in the ‘duties of the clergy,’ but becomes, like the clergy, their responsibility. This paper, therefore discusses the theological basis of lay ministry as co-responsibility in the mission of the Church, emphasising the importance of ‘coresponsibility’ as an ongoing self-understanding of the Church as a community of God’s people who are partakers in the priesthood of Christ by virtue of their baptism. It discusses active participation of the laity in the mission of the Church as a way of pastoral renewal and growth of the Church and accomplishment of its mission as agent of the new evangelisation. The article therefore recommends proper formation of the laity for the accomplishment of the divine mission.